K.S.U aerobic swine-waste handling system (6 years of problems and progress) - Koch, B.A.; Allee, G.L.; Lipper, R.I.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The Kansas State University Swine research Unit's aerobic-oxidation waste disposal system is functioning satisfactorily with minimum maintenance and supervision. Labor requirements are low. Odor is no problem. Waste fluid can be spread on the fields any time without creating a "public nuisance.” Pigs are performing satisfactorily in the unit. Flies are easily controlled and suitable sanitation is easily maintained.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Swine-waste handling system; Fly control